PERBANDINGAN HASIL BELAJAR MELALUI NHT DAN MM DENGAN MEMPERHATIKAN AQ SISWA - Fitri Ahadiyah; Tedi Rusman; Darwin Bangun (FKIP Unila, 2014)
TThis study aims to find out: 1)difference of learning results by using NHT, MM. 2) interaction between the learning model and adversity intelligence of the results of the study. 3)differences between learning outcomes model of learning in students with high adversity intelligence. 4)difference of learning outcomes between the learning model on students with adversity intelligence. 5)differences of learning outcomes between the learning model in students with low adversity intelligence. Experimental methods of comparative approaches. Data collecting tests are used and 61 questionnaires. Research results: 1)there are differences in the results of learning to use NHT and MM. 2)there are interactions between the learning model with adversity intelligence against the results of the study. 3)there is no difference between learning model results in students with high adversity intelligence. 4)there is a difference between learning model results in students with intelligence being adversity. 5)there is a difference between learning model results in students with lower adversity intelligence.Penelitian ini bertujuan mengetahui: 1)perbedaan hasil belajar menggunakan NHT, MM. 2) interaksi antara model pembelajaran dan kecerdasan adversitas terhadap hasil belajar. 3)perbedaan hasil belajar antar model pembelajaran pada siswa dengan kecerdasaan adversitas tinggi. 4)perbedaan hasil belajar antar model pembelajaran pada siswa dengan kecerdasaan adversitas sedang. 5)perbedaan hasil belajar antar model pembelajaran pada siswa dengan kecerdasaan adversitas rendah. Metode eksperimen pendekatan komparatif. Pengumpul data tes dan angket 61 siswa. Hasil penelitian: 1)ada perbedaan hasil belajar menggunakan NHT dan MM. 2) ada interaksi antara model pembelajaran dengan kecerdasan adversitas terhadap hasil belajar. 3)tidak ada perbedaan hasil belajar antar model pada siswa dengan kecerdasan adversitas tinggi. 4)ada perbedaan hasil belajar antar model pada siswa dengan kecerdasan adversitas sedang. 5)ada perbedaan hasil belajar antar model pada siswa dengan kecerdasan adversitas rendah.Kata kunci: aq, hasil belajar, mm, nht.